Peran Sprinkler Water dalam Rencana Darurat Kebakaran Bandara: Evaluasi Protokol dan Langkah-langkah Mitigasi Risiko - Wardhani, Shauqi Nazla; Saputra, Surya Tri; Adinnagara, Muhammad Satria (Politeknik Penerbangan Indonesia Curug, 2024)
This study evaluates the role of water sprinkler systems in airport fire emergency plans, as well as the related protocols and risk mitigation measures. Airports have a high risk of fire due to the presence of aircraft fuel and refueling equipment. The water sprinkler system is a key component of the fire suppression system that works automatically to detect and extinguish fires. This study uses a literature analysis method to evaluate the effectiveness, reliability, and efficiency of sprinkler systems in protecting airport infrastructure and passengers. The results show that water sprinkler systems are highly effective in early fire detection, preventing fire spread, and protecting airport assets. The protocol evaluation emphasizes the importance of compliance with safety standards, proper design and installation, and regular testing and maintenance. Risk mitigation measures include regular inspections, the use of backup fire detection systems, clear emergency procedures, and collaboration with firefighting personnel. In conclusion, if properly installed and managed, water sprinkler systems can significantly enhance safety and protect airport assets from fire threats.